Smartphone-based mobile assisted language learning application in higher vocational education in Indonesia - Mutiaraningrum, Ira; Nugroho, Arif (JEES (Journal of English Educators Society), 2021)
This study sought to examine the educational affordance and constraints of smartphone-based assistive technology in language learning from the students’ point of view along with their recommendations on the possible future advancement of smartphone-based assistive technology to help students engage better. This study employed content analysis in analyzing the data obtained from open-ended questions administered to students. The findings of this study denote the use of smartphones in widening vocabulary range, providing practices for English exercise, having attractive and interactive features, and fostering autonomy, self-regulation, and independence learning due to its practicality, portability, accessibility, and flexibility. This study highlights technical problems and confusion as the obstacles emerging from the use of smartphones in language learning. Meanwhile, the recommendations for future smartphone-based application updates are discussed in detail. All in all, smartphone-based assistive language learning application is fruitful for students and is recommended to be used for vocational higher education students as the part of informal learning during the COVID-19 pandemic situation. HIGHLIGHTS: Language learning has stepped forward to more personal learning tools by integrating smartphones as an aid for mobile learning. smartphones are fruitful in widening vocabulary range, providing practices for English exercise, having attractive and interactive features, and fostering autonomy, self-regulation, and independence learning due to its practicality, portability, accessibility, and flexibility. From language learning mobile application, students demanded simpler reading exercises and vocabularies and slower listening practice in the applications.